Association between Hyperoche martinezii (Amphipoda: Hyperiidae) and ctenophores from the Buenos Aires coast, Argentina (South-western Atlantic Ocean) - Puente Tapia, Francisco Alejandro (2016)
This survey examined the association between the hyperiid amphipod Hyperoche martinezii and ctenophores off the Argentinian coast (38°08′17″S, 57°31′18″W) through the evaluation of seasonality, prevalence and intensity of infection during an annual cycle. Medusae were also examined but only the ctenophores Mnemiopsis leidyi, Pleurobrachia pileus and Beroe ovata showed this association during the austral mid-spring to mid-summer. A total of 502 hyperiids were obtained; most (422 individuals) were larval stages, 53 juveniles and 27 adults. Mnemiopsis leidyi had the highest number of hyperiids with 98.6%, followed by P. pileus (0.80%), and B. ovata (0.60%). Total prevalence was 2.0 and intensity of infection ranged between 1 and 17 hyperiids per ctenophore. The host with highest prevalence was B. ovata (4.54), followed by M. leidyi (3.76) and P. pileus (0.1). Prevalence values had some correlations with the increase in the total length of B. ovata (r = 0.480, P = 0.006) and M. leidyi (r = 0.501, P < 0.001), and between total length and intensity in B. ovata (r = 0.425, P = 0.017). The hyperiid was found in different parts of the host body: larval stages were found in the canal close to the subtentacular comb row and the stomodeum, whereas juvenile/adult stages were observed with a resting posture on the external surface of the ctenophores. The known geographic distribution of H. martinezii was extended; this finding represents the addition of three new hosts for this hyperiid.